Epidemiological changes in anti-glomerular basement membrane disease in Madrid in the context of the COVID-19 pandemic - León-Machado, Lina; Sierra-Torres, Gonzalo; Shabaka, Amir; Cases-Corona, Clara; Vega, Cristina; Rivas, Begoña; Ruiz Cabrera, Diana; Fernandez-Juarez, Gema (Frontiers in Nephrology, 2025)
IntroductionRecent studies in Europe have reported a rising incidence in anti-glomerular basement membrane (anti-GBM) disease, potentially linked to demographic shifts or environmental factors. This study aimed to assess temporal trends in incidence, clinical presentation, and outcomes of anti-GBM disease in two urban areas of Madrid over the past two decades.Materials and methodsWe conducted a retrospective observational study of patients diagnosed with anti-GBM disease between 2006 and 2022 at two urban areas covering 884,000 residents in Madrid. Inclusion required confirmed anti-GBM antibodies with clinical manifestations. Incidence was calculated per 1,000,000 person-years. Data were analyzed across six time periods and compared pre- and post-COVID-19 onset.ResultsA total of 26 cases were identified (mean age 52 ± 26 years; 54% female). Incidence increased from 1.13 cases per million persons-year before 2020, to 4.53 cases per million persons-year after 2020 (p<0.001). No differences were observed in demographic data or environmental exposures over time. Post-COVID-19 cases had lower serum creatinine at presentation (5.09 ± 4 vs. 8.7 ± 3.9 mg/dL, p=0.037), more pulmonary involvement (83.3% vs. 35.7%, p=0.039), and better 1-year renal survival (50% vs. 14.3%, p=0.049). Overall patient survival did not differ between groups.ConclusionsIncidence of anti-GBM disease has increased in Madrid, particularly after the COVID-19 pandemic. Improved renal survival appears linked to earlier diagnosis and management, rather than changes in environmental exposure. These findings highlight the importance of heightened clinical awareness for early detection and treatment of this aggressive disease.